Status dan Kedudukan SHM Satuan Rumah Susun Pasca Kebakaran: Pusat Perbelanjaan Makassar Mall - M. Ridjal Adelansyah Syam; Abd. Kahar Muzakkir (SIGn Jurnal Hukum, 2022)
This study will examine and analyze the status and position of the SHM of Condominium Units in the building Blok-A of Makassar Mall after a fire. This research combines normative juridical and empirical research methods. The primary data were collected using direct interviews, while the secondary data was collected using literature study techniques. The data obtained in this research were then analyzed qualitatively. The results show that the SHM of Condominium Units in building Blok-A of Makassar Mall is still in the status quo. Meanwhile, the fire phenomenon and implementation of the construction of the new building Blok-A of Makassar Mall cannot be qualified as a requirement for the removal of the SHM of Condominium Units. In this case, implementing that construction is a form of PT. MTIR’s obligation to the Makassar Municipal Government based on the agreement held under the BOT system. In contrast, PT. MTIR made efforts to usurp the rights owned by traders as holders of SHM of Condominium Units in the building Blok-A of Makassar Mall. Therefore, it is recommended that the Makassar Municipal Government re-evaluate the involvement of PT. MTIR as the Holder of the Right to Build for Makassar Mall Shopping Center. In addition, it is recommended that PT MTIR register for the transfer of the right based on Government Regulation No. 24 of 1997 if they continue to impose their will to become the holder of the SHM of Condominium Units in building Blok-A of Makassar Mall. Furthermore, it is recommended that law enforcement agencies conduct investigations related to the Collaboration Agreement No. 44/511.2/SP/HK along with the accompanying addendums. In this case, traders must get legal certainty and protection as holders of SHM of Condominium Units in the building Blok-A of Makassar Mall.